2020
DOI: 10.1039/c9ra09032k
|View full text |Cite
|
Sign up to set email alerts
|

Lower Mg and S contents in solar salt used in kimchi enhances the taste and anticancer effects on HT-29 colon carcinoma cells

Abstract: The anticancer effects of kimchi prepared with different kinds of solar salts were evaluated in an in vitro cellular system using HT-29 human colon carcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…This is consistent with research results showing that ingestion of WDSD effectively suppressed colon cancer by regulating the protein expression of various factors related to cancer cell development and growth, such as apoptosis and cell cycle arrest [20]. Yu et al [37] and Park et al [38] reported that the anticancer and antiobesity functionality of kimchi manufactured with washed and dehydrated sea salt was improved, because bittern was removed through washing and dehydration during the manufacturing process of sea salt, and minerals such as Mg and S were removed. Our experimental results likewise suggest that the anticancer effect observed in doenjang made with washed-dehydrated solar salt may be attributed to the same factors.…”
Section: Effects Of Wdsd On Mrna Expression Of the Apoptosisrelated G...supporting
confidence: 90%
“…This is consistent with research results showing that ingestion of WDSD effectively suppressed colon cancer by regulating the protein expression of various factors related to cancer cell development and growth, such as apoptosis and cell cycle arrest [20]. Yu et al [37] and Park et al [38] reported that the anticancer and antiobesity functionality of kimchi manufactured with washed and dehydrated sea salt was improved, because bittern was removed through washing and dehydration during the manufacturing process of sea salt, and minerals such as Mg and S were removed. Our experimental results likewise suggest that the anticancer effect observed in doenjang made with washed-dehydrated solar salt may be attributed to the same factors.…”
Section: Effects Of Wdsd On Mrna Expression Of the Apoptosisrelated G...supporting
confidence: 90%
“…In addition, kimchi sensory evaluation was carried out using the 9‐point scale method when the 3‐week fermented kimchi at 5°C reached the optimally ripened stage (acidity 0.4–0.9) (Yu et al., 2020). As a result, in subjective items, the overall acceptability of AK (6.83) was higher than that in SK (4.17) and AmK (6.23) groups (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Acidity was titrated by adding 0.1 N NaOH until the pH was 8.4 by diluting the sample 20 times according to the AOAC standard test method, and the amount of 0.1 N NaOH consumed was measured in milliliters (mL). The optimal value is expressed in terms of % of lactic acid (Yu et al., 2020). Acidity0.333333em\%=mL of0.333333em0.10.333333emN NaOH×normality of NaOH×0.09weight of sample0.333333emnormalg×100…”
Section: Methodsmentioning
confidence: 99%